Relieving the effect of static load errors in nonlinear vibration isolation mounts through stiffness asymmetries. (17th March 2015) - Shaw, A.D.; Neild, S.A.; Friswell, M.I.
Abstract: High Static Low Dynamic Stiffness (HSLDS) mounts consist of nonlinear springs that support a high static load with low static displacement, whilst maintaining locally low stiffness near equilibrium, to give a low natural frequency and consequently good isolation properties. Recent analysis has investigated such devices when the force–displacement relationship is an odd function about the equilibrium position, and analysed the consequences of different shapes of these functions. However many devices that have the HSLDS characteristic do not meet the assumptions of this analysis, in that the force–displacement relationship is generally asymmetric about equilibrium. Furthermore, even devices that do meet this assumption may be subject to significant adjustment error, particularly in the context of air vehicles where manoeuvres such as banked turns can cause an apparent variation in gravitational acceleration, and a consequent variation in the weight of the payload. This change in static load moves the payload away from its intended region of low stiffness. The current paper provides analysis of these situations, and shows that the performance of a mount with a symmetric stiffness–displacement relationship is highly sensitive to errors in the static loading. It is then shown that a mount with an asymmetric stiffness–displacement function can offer significant performance advantages when there are adjustment errors in the loading of the mount.